Under the radar: co-introduced monogeneans (Polyopisthocotylea: Gastrocotylinea) of the invasive fish Scomberomorus commerson in the Mediterranean Sea. - Rothman, S.B.S., A. Diamant & M. Goren (Parasitology Research, 2022)
The Levant Basin is in many ways the world's most invaded marine ecosystem owing to the existence of the man-made Suez Canal. The invasion of free-living organisms through this pathway is increasingly documented and monitored in the past two decades, and their ecological impact recognized. Nonetheless, while tremendous scientific effort is invested in documenting introduced fishes, co-introduction events of these fishes and their parasites have drawn relatively little interest. In our research, we examined the presence of gill parasites (Monogenea) on the invasive narrow barred Spanish mackerel Scomberomorus commerson which has been known in the Mediterranean Sea for 80 years. The gills of S. commerson supported numerous, relatively large monogeneans (Monogenea: Gastrocotylinea), reaching prevalence levels of 100% with a mean intensity of similar to 80 worms per host. Using an integrated molecular and morphological approach, four gastrocotylinean species were identified: Gotocotyla acanthura, Cathucotyle cathuaui, Pricea multae, and Pseudothoracocotyla ovalis. Two species, C. cathuaui and P. ovalis, are reported here for the first time from the Mediterranean. Sequences of the 28S rRNA gene of G. acanthura from native hosts, Pomatomus saltatrix and Trachinotus ovatus, differed from individuals collected from S. commerson by 1.8%. We therefore suggest that the taxonomic status and distribution of G. acanthura should be revisited, and we recommend an integrated approach as essential to accurately detect co-introductions.